Polystyrene microplastics alter bioaccumulation, and physiological and histopathological toxicities of cadmium in the polychaete Perinereis aibuhitensis - Cong, Yi; Lou, Yadi; Zhao, Huan; Li, Zhaochuan; Zhang, Mingxing; Jin, Fei; Wang, Ying; Wang, Juying (Frontiers in Marine Science, 2022)
Heavy metal (HM) pollution in the marine environment has been of concern for decades. The potential impact of HMs carried by emerging marine pollutants such as microplastics (MPs) has attracted attention only in recent years. In this study, we investigated the single and combined chronic toxic effects (growth, burrowing behavior, and histopathology) of cadmium (Cd, three concentrations of low, medium, and high) and polystyrene (PS) microspheres (1 μm, 10 μg/L) on the coastal polychaete Perinereis aibuhitensis. Cd bioaccumulation under two exposure scenarios was also explored. Our results showed that Cd and PS did not affect worm growth for single or combined exposure, while 13.08 μg/L of Cd (CdL) alone significantly decreased the burrowing time of P. aibuhitensis in sediment. The presence of PS mitigated the hormetic effect of Cd on worm burrowing behavior, and this influence was Cd concentration-related. Cd body burdens in worms exposed to the medium and high Cd concentrations (CdM and CdH) were significantly greater than those of control worms with or without the presence of PS. In addition, Cd bioaccumulation was significantly higher with the coexistence of PS than those of Cd alone at the CdL and CdM groups. Histopathological analyses demonstrated a trend of epidermal and intestinal damages for single Cd/PS and their combined groups, and the contribution of PS-MPs should not be ignored. Our results indicate that the toxic effects and bioaccumulation pattern of Cd could be altered with the presence of PS-MPs for P. aibuhitensis, especially at environmentally relevant concentrations.